Hypothalamic Hamartomas: Evolving Understanding and Management. (2nd November 2021) - Cohen, Nathan T.; Cross, J. Helen; Arzimanoglou, Alexis; Berkovic, Samuel F.; Kerrigan, John F.; Miller, Ilene Penn; Webster, Erica; Soeby, Lisa; Cukiert, Arthur; Hesdorffer, Dale K.; Kroner, Barbara L.; Saper, Clifford B.; et al.
Abstract : Hypothalamic hamartomas (HH) are rare, basilar developmental lesions with widespread comorbidities often associated with refractory epilepsy and encephalopathy. Imaging advances allow for early, even prenatal, detection. Genetic studies suggest mutations in GLI3 and other patterning genes are involved in HH pathogenesis. About 50%–80% of children with HH have severe rage and aggression and a majority of patients exhibit externalizing disorders. Behavioral disruption and intellectual disability may predate epilepsy. Neuropsychological, sleep, and endocrine disorders are typical. The purpose of this article is to provide a summary of the current understanding of HH and to highlight opportunities for future research.